2021
DOI: 10.1111/all.15161
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor acetylhydrolase: A biomarker in Hymenoptera venom allergy?

Abstract: 6. Palomares O, Ruckert B, Jartti T, et al. Induction and maintenance of allergen-specific FOXP3+ Treg cells in human tonsils as potential first-line organs of oral tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…They found PAF‐AH activity was significantly lower in HVA than in healthy people 83 . Most recently, Bilo et al 84 reported serum PAF‐AH levels had no correlation with the severity of reaction observed in their HVA patients. They again confirmed that compared to healthy controls, PAF‐AH was significantly lower in HVA patients ( p < 0.001), and they also found PAF‐AH was lower than controls in asthma patients ( p = 0.001) and patients with rhinitis ( p = 0.014).…”
Section: Adult and Pediatric Data Of Paf/paf‐ah In Various Disease St...mentioning
confidence: 95%
See 1 more Smart Citation
“…They found PAF‐AH activity was significantly lower in HVA than in healthy people 83 . Most recently, Bilo et al 84 reported serum PAF‐AH levels had no correlation with the severity of reaction observed in their HVA patients. They again confirmed that compared to healthy controls, PAF‐AH was significantly lower in HVA patients ( p < 0.001), and they also found PAF‐AH was lower than controls in asthma patients ( p = 0.001) and patients with rhinitis ( p = 0.014).…”
Section: Adult and Pediatric Data Of Paf/paf‐ah In Various Disease St...mentioning
confidence: 95%
“…Allergic/urticarial Anaphylaxis 23 High PAF and low PAF-AH at time of anaphylaxis associated with severe (vs. less mild or moderate) anaphylaxis 6 Low PAF-AH associated with fatal anaphylaxis 6 Low basal PAF-AH associated with severe anaphylaxis from Hymenoptera venom 82 PAF-AH was lower in adults with hymenoptera venom allergy than controls 83,84 PAF-AH was lower in children with severe anaphylaxis than mild-moderate 18 and was not altered from basal levels during anaphylaxis Transcriptional activity of the PAF-AH gene was lower in children with moderate anaphylaxis than in mild anaphylaxis or other controls 85 Allergic rhinitis 86 PAF elevated at baseline and after allergen nasal challenges Chronic urticaria 87 PAF levels elevated and PAF-AH decreased in patients refractory to antihistamines versus normal healthy controls…”
Section: Condition Detailsmentioning
confidence: 99%
“…PAF is a potent proinflammatory mediator involved in the pathophysiology of several allergic diseases, including asthma and anaphylaxis 10 . PAF is biosynthesized by two distinct pathways: a remodeling or de novo pathway 23–26 .…”
Section: Discussionmentioning
confidence: 99%
“…PAF is known to be involved in the pathogenesis of anaphylaxis, depending on the stimuli 2,3 . PAF acts by binding to its specific PAF receptor and is rapidly inactivated and eliminated by PAF acetylhydrolase (PAF‐AH) in the circulation (the half‐life time of PAF: 3–13 min) 7,9,10 . Moreover, serum PAF levels are significantly higher in anaphylactic patients than in control patients and inversely correlate with PAF‐AH activity 11 .…”
Section: Introductionmentioning
confidence: 99%
“…PAF stimulates mast cells 23 and eosinophils, 24–26 and has been implicated in allergic conditions 27 such as anaphylaxis, 28–30 chronic spontaneous urticaria (CSU), 31–33 immediate and late cutaneous reactions, 34 and rhinitis 35–39 . Elevated PAF levels were strongly associated with severe anaphylaxis, more so than histamine or tryptase 28 .…”
mentioning
confidence: 99%